The International Law of Protection and Promotion of Human Rights: Past, Present and Future Part 2 - D. V. Ivanov; E. V. Tarasyants (Московский журнал международного права, 2009)
In the second part of the article its authors continue their research in the field of International Law of Protection and Promotion of Human Rights. They analyze the mechanisms of control over execution of human rights within UNESCO and ILO. Furthermore a concise overview of conventional control bodies is given (Human Rights Committee, Committee on Economic, Social and Cultural Rights, Committee on the Rights of the Child etc.). The article describes international mechanisms for protection of human rights on the regional level. It also covers new trends and developments in the field of International Human Rights Law, e.g. establishment of new protection mechanisms and procedures (in particular Human Rights Council), emergence of new human rights, development of the concept of indigenous peoples’ rights, reform of UN human rights protection mechanism, extension of international courts’ competence, humanitarian intervention. The article also concerns situation with human rights in Russia.